Philosophical Values and Processes of Religious Tolerance in Nyarumkop Village, Singkawang, West Kalimantan - Mustansyir, Rizal; Tazkiyah, Era (Humaniora: Journal of Indonesia Culture and Society, 2025)
The purpose of the research is to provide a description and analysis of the processes that led to the establishment of philosophical ideals and tolerance in the Nyarumkop village in Singkawang, West Kalimantan. The research technique employed is qualitative, based on Paul Ricœur's hermeneutic-phenomenological approach. This methodology aims to understand the significance embedded in the symbol of tolerance, which is linked to the context of social existence. In addition, the Aristotelian method of philosophical inquiry employs the Golden Mean as the Middle Way between two extreme poles in the process of decision-making or action-taking, which ultimately leads to arete, which is synonymous with perfection. Several religious leaders from Nyarumkop Village were interviewed to determine the information based on the criteria provided by the researchers. During the research, the methods used for data collection included documentation, interviews, and observation. The findings of the research suggest that tolerance is the key to achieving harmony within the Nyarumkop village, which is renowned for its rich religious and ethnic diversity. Religious discussion is a crucial component in fostering tolerance and understanding. The Nyarumkop village holds four significant parts of the philosophical principles. These include the spirit of kinship, friendship, mutual collaboration, and the empowerment of communal life via the economy, as well as tourism's role in Nyarumkop village.